Impact of nutrient enrichment on productivity of coastal water along the SE Mediterranean shore of Israel - A bioassay approach. (February 2018) - Rahav, Eyal; Raveh, Ofrat; Hazan, Or; Gordon, Nurit; Kress, Nurit; Silverman, Jacob; Herut, Barak
Abstract: The coastal waters of the southeastern Mediterranean-Sea (SEMS) are routinely enriched with naturally-occurring and anthropogenic land-based nutrient loads. These external inputs may affect autotrophic and heterotrophic microbial biomass and activity. Here, we conducted 13 microcosm bioassays with different additions of inorganic NO3 -(N), PO4 -(P) and Si(OH)4 -(Si) in different seasons along the Mediterranean coast of Israel. Our results indicate that cyanobacteria are mainly N-limited, whereas N or Si (or both) limit pico-eukaryotes. Furthermore, the degree to which N affects phytoplankton depends on the ambient seawater's inorganic N and N:P characteristics. Heterotrophic bacteria displayed no response in all treatments, except when all nutrients were added simultaneously, suggesting a possible co-limitation by nutrients. These results contrast the N + P co-limitation of phytoplankton and the P-limitation of bacteria in the open waters of the SEMS. These observations enable the application for a better science-based environmental monitoring and policy implementation along the SEMS coast of Israel. Highlights: Coastal water autotrophs are sensitive to anthropogenic N inputs. Ambient N and N:P ratio affect the type and magnitude of the phytoplankton response. P alone has no effect on microbial populations and production rates. Primary and bacterial production is essential indicators for monitoring water quality.